Dreams come true - Chapman, Linda; Hull, Biz (London : Puffin, 2002)
Lauren helps Twilight figure out how to use his unicorn magic to give courage to a pony who is afraid of jumping.
Keywords: Ponies -- Juvenile fiction; Unicorns -- Juvenile fiction; Magic -- Fiction; Ponies -- Fiction; Self-confidence -- Fiction; Unicorns -- Fiction